DEVELOPMENT OF THE MANAGEMENT AND FINANCING SYSTEM OF GENERAL SECONDARY EDUCATION INSTITUTIONS - Рамський, Андрій Ю.; Казак, Оксана О. (Journal of Strategic Economic Research, 2023)
In the presented work, the main aspects of the development of general secondary education institutions are considered, the peculiarities of their financing and further ways of development are determined. The transition of educational institutions to the innovative path of development in order to ensure their adaptation to modern globalization and integration processes is of particular importance under modern economic conditions and the development of educational processes in the world. The purpose of the presented work is to study the key aspects of the development of general secondary education institutions and possible ways of providing additional financing of educational processes in them. The main methods of research are analysis and synthesis to determine the features of the development of institutions of general secondary education, deduction and induction for the interpretation of opportunities for the development and financing of institutions of general secondary education, a graphic method for visual display of the presented research. The basis of the financial system is the formation of the institution's budget. The budget should take into account the needs of the institution in various areas, such as payment of teaching staff, development of infrastructure, purchase of educational materials and security. The management and financing system should ensure the efficient use of financial and human resources. Resources should be allocated in such a way as to meet the needs of students and support the development of the institution. Interaction with the community, parents, and students is an important aspect of school management. Public involvement in funding and development decisions helps to create an environment conducive to the successful functioning of an institution. The development of the system of management and financing of institutions of general secondary education contributes to the improvement of the quality of education and preparation of the young generation for life in the modern world. The optimal use of resources, the creation of a favorable environment for the development of the intellectual potential of students and the teaching staff are important factors in the effective functioning of an educational institution.